2013
DOI: 10.1177/0021955x13477434
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional polyetherimide nanocomposite foam

Abstract: Polyetherimide/multi-wall carbon nanotube nanocomposite foams were fabricated and their electrical and mechanical properties characterized. The composites with 0.5–3 wt% of carbon nanotube loadings were fabricated using a solution-based method. Different foaming conditions were studied along with the residual solvent effects. It was found that the residual solvent significantly affected the mechanical properties of the nanocompsites. Electrical conductivity of the composite foams with the same wt% loading of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Specifically, the incorporation of pores in nanocomposites was responsible for a more dense filler network, with shorter path for electron transport, less electron scattering, and thus increased conductivity and reduced percolation threshold [23]. Kim et al reported experimental studies of polymer foams incorporating CNTs [24,25]. The authors observed an increase in electrical conductivity and decrease in percolation threshold with porosity when considering a fixed filler amount.…”
Section: Electrical Percolation In Hybrid Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the incorporation of pores in nanocomposites was responsible for a more dense filler network, with shorter path for electron transport, less electron scattering, and thus increased conductivity and reduced percolation threshold [23]. Kim et al reported experimental studies of polymer foams incorporating CNTs [24,25]. The authors observed an increase in electrical conductivity and decrease in percolation threshold with porosity when considering a fixed filler amount.…”
Section: Electrical Percolation In Hybrid Systemsmentioning
confidence: 99%
“…Similar experimental observations and interpretations have been reported by Tran and coworkers [27,28] and Zhi et al [29] for porous nanocomposites incorporating multiwalled CNTs. Some processing techniques using high aspect ratio fillers, including CNTs [25] and GNPs [30], can result in a morphology characterized by highly oriented fillers. Experimental observations have shown that electrical conductivity depends on filler alignment in solid nanocomposites.…”
Section: Electrical Percolation In Hybrid Systemsmentioning
confidence: 99%
“…It is also possible to guarantee samples of exactly the same density by foaming in a closed mold, thus limiting the expansion to a pre-specified value. 2931 Even in such cases, however, a density gradient between the core and the walls 3236 may provide misleading results. In extreme cases, the formation of a skin at the surface may significantly affect mechanical measurements, especially if the foam density is very low.…”
Section: Accounting For Differences In Foam Densitymentioning
confidence: 99%
“…High-performance polymer matrices could be used, such that the resultant nanocomposite foams could be employed in a more stringent environment where high-service temperatures are required. Kim and Li (2013) fabricated PEI/MWCNT nanocomposite foams and characterized their electrical and mechanical properties. PES is an amorphous polymer having a glass transition temperature (T g ) of 225 °C and a density of 1.37 g/cm 3 .…”
Section: Polymer Nanocomposite Foamsmentioning
confidence: 99%